2000
DOI: 10.1001/jama.283.16.2128
|View full text |Cite
|
Sign up to set email alerts
|

Acute Onset of Decreased Vision and Hearing Traced to Hemodialysis Treatment With Aged Dialyzers

Abstract: Severe patient injury was associated with exposure to aged cellulose acetate membranes of dialyzers, allowing cellulose acetate degradation products to enter the blood. Clinicians should be aware that aged cellulose acetate membranes may cause severe adverse reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 17 publications
4
35
0
Order By: Relevance
“…However, our study has shown significant depression in hearing threshold after 3 sessions of hemodialysis. Also, the presence of correlation between the post-treatment pure tone threshold and duration of illness and serum creatinine levels which was not found with the dosage of diuretics and blood pressure is similar to the report of Gatland et al [5] and Hutter et al [6]. Gatland et al [5] reported decrease in threshold in 22/31 ears after dialysis but found no correlation with weight changes.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…However, our study has shown significant depression in hearing threshold after 3 sessions of hemodialysis. Also, the presence of correlation between the post-treatment pure tone threshold and duration of illness and serum creatinine levels which was not found with the dosage of diuretics and blood pressure is similar to the report of Gatland et al [5] and Hutter et al [6]. Gatland et al [5] reported decrease in threshold in 22/31 ears after dialysis but found no correlation with weight changes.…”
Section: Discussionsupporting
confidence: 85%
“…The cochlea in patients under the treatment with hemodialysis has been reported to be susceptible to various insults and the patients frequently exhibit some degree of sensorineural hearing loss, although the responsible etiological factor(s) still remain controversial [5,6]. In addition, the concurrent existence of these factors in each patient make conclusions difficult on the significance of each variable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An investigation by the CDC and the FDA identified the use of old cellulose acetate (CA) dialyzers as the common link in this incident. 1 Toxic degradation products of CA dialysis membranes were identified as the likely cause of this tragedy. This hypothesis was based on a number of premises.…”
Section: Introductionmentioning
confidence: 99%